Atypically heterogeneous vertical first fixations to faces in a case series of people with developmental prosopagnosia. Issue 4 (20th April 2020) - Wilcockson, Thomas D.W.; Burns, Edwin J.; Xia, Baiqiang; Tree, Jeremy; Crawford, Trevor J.
ABSTRACT: When people recognize faces, they normally move their eyes so that their first fixation is in the optimal location for efficient perceptual processing. This location is found just below the centre-point between the eyes. This type of attentional bias could be partly innate, but also an inevitable developmental process that aids our ability to recognize faces. We investigated whether a group of people with developmental prosopagnosia would also demonstrate neurotypical first fixation locations when recognizing faces during an eye-tracking task. We found evidence that adults with prosopagnosia had atypically heterogeneous first fixations in comparison to controls. However, differences were limited to the vertical, but not horizontal, plane of the face. We interpret these findings by suggesting that subtle changes to face-based eye movement patterns in developmental prosopagnosia may underpin their face recognition impairments, and suggest future work is still needed to address this possibility.